Speech acts in undergraduate thesis defenses: A pragmatic analysis of oral interaction in an EFL context - Imanuel Kamlasi; Edmundus Bouk; Hendi Pratama; Sri Wahyuni; Seful Bahri (EduLite: Journal of English Education, Literature and Culture, 2026)
The study argues that institutional power dynamics influence speech acts in the EFL thesis defenses. The study identifies types of speech acts used by examiners and candidates and analyzes how these acts shape the dynamics of the defenses. The research utilized qualitative methods based on the Interaction Analysis Method. Eight EFL candidates and eleven examiners were involved in the research. The study used an observation guide and audio/video recorders to document oral interactions during thesis defense sessions. The oral interactions were transcribed for analyses. The utterances were coded and analyzed using Austin's and Searle's framework of speech acts. The findings indicate a clear power asymmetry between the examiner and the candidate. The examiners confirmed that directive speech acts are dominant with 53%, followed by assertive speech acts at 35%. Expressive speech acts account for 10%, while commissive and declarative speech acts are low, only 1%. The candidates showed that assertive speech acts are the most prevalent of 86%, expressive acts represent 10% while directive acts are significantly lower at 3%. Commissive acts make up 1%, and declaration acts are the least common. The study suggests targeted training to minimize misunderstanding in an academic discussion.